2017
DOI: 10.1088/1741-2552/aa6a5f
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the response of small myelinated axons in a compound nerve to kilohertz frequency signals

Abstract: Objective There is growing interest in electrical neuromodulation of peripheral nerves, particularly autonomic nerves, to treat various diseases. Electrical signals in the kilohertz frequency (KHF) range can produce different responses, including conduction block. For example, EnteroMedics’ vBloc® therapy for obesity delivers 5 kHz stimulation to block the abdominal vagus nerves, but the mechanisms of action are unclear. Approach We developed a two-part computational model, coupling a three-dimensional finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 76 publications
5
82
0
Order By: Relevance
“…We developed an approach whereby we modeled rheobase thresholds, namely the response to a long duration pulse. This allowed us, as a first approximation, to remove considerations of neuron dynamics and stimulation train parameters such a number, pulse shape, frequency, and duty‐cycle which while important would incur a large set of additional fiber specific parameterizations —whereas our focus was to address the role of tissue modeling. The assumption also supports future efforts to optimize stimulation approaches leveraging linearity (see “Discussion” section).…”
Section: Methodsmentioning
confidence: 99%
“…We developed an approach whereby we modeled rheobase thresholds, namely the response to a long duration pulse. This allowed us, as a first approximation, to remove considerations of neuron dynamics and stimulation train parameters such a number, pulse shape, frequency, and duty‐cycle which while important would incur a large set of additional fiber specific parameterizations —whereas our focus was to address the role of tissue modeling. The assumption also supports future efforts to optimize stimulation approaches leveraging linearity (see “Discussion” section).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, how neurons respond to kHz frequencies remains an open question (Pelot et al . ; Crosby et al . ; Dmochowski and Bikson, ; Li et al .…”
Section: Promise and Pitfalls Of Khz Stimulationmentioning
confidence: 99%
“…kHz fluctuations in membrane potential) are of interest (Pelot et al . ); and (4) when interactions between equipment and the body introduce complex distortions (Neuling et al . ; Noury and Siegel, ; Gebodh et al .…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…This seemingly trial and error approach to electrode placement and stimulation parameters highlight the need for robust models that integrates the type and site of electrode placement coupled with electrophysiological properties of the targeted neurons. This type of modeling has recently been applied to understanding the failure of kilohertz frequency blockade to achieve primary clinical endpoints as a therapy in obesity . Such analysis indicated that the selected parameters based on prior assumptions of electrophysiological properties of the nerve would appear to be ineffective, or could result in stimulation rather than blockade .…”
Section: Clinical Trials; Clinical Challenges and Opportunitiesmentioning
confidence: 99%
“…61 Such analysis indicated that the selected parameters based on prior assumptions of electrophysiological properties of the nerve would appear to be ineffective, or could result in stimulation rather than blockade. 61 With the use of unique electrodes, electrode placement, and stimulation parameters perhaps the variability in clinical outcomes should not be surprising. These issues remain unique challenges and opportunities for the continued development of therapeutic electroceutical device for practical application in the clinic.…”
Section: Clinical Trials; Clinical Challenges and Opportunitiesmentioning
confidence: 99%